Menuju Sistem e-Goverment Terpadu dan Handal Berbasis Cloud Computing - Didik Widianto, Eko (JURNAL SISTEM KOMPUTER, 2011)
Traditional and centric approach which use dedicated server to host e-Goverment applications makes the cost of the solution becoming high, underutilized computing resources (inefficiency) and cannot fulfill requirements to deliver fourth level deployment of eGovernment, regarding to its integrated services, reliability, interoperability and availability. This research provides a framework to implement cloud computing for integrated and reliable e-Government system. Cloud model has been developed. Its implementation platform using open source software are also identified. Finally, further research to realize this community-type of cloud is challenged.Index Terms—e-Goverment, cloud computing, distributed system, information technology, pervasive computing